PLANT APPRAISALS–THEIR TREATMENT IN THE ACCOUNTS. - Hull, G. L.; Konopak; Hurst; Dalton (The Accounting Review, 1927)
During the past few years there has been a considerable amount of writing and discussion in the accounting and engineering field on the subject of the valuation of assets, and especially has the valuation of fixed plant assets come in for much analysis and study. The increasing interest in this problem has been doubtless due, in no small measure, to the attention directed toward it by the income tax regulations and by the marked upward swing of prices from the prewar to the postwar level-a fact which has been of considerable importance and annoyance in numerous public utility valuations incident to the regulation of their rates. However, it may be said without fear of serious contradiction that, as a practical matter, the accountant in the past has not given sufficient consideration to this important problem. This article sets forth the various methods by which the facts of such a policy may be expressed in the accounts and operating statements, assuming that the policy has been decided upon.